Hubungan Antara Pet Attachment dengan Happiness Pada Masa Dewasa Awal - Hasanah, Dalilah Al; Daud, Muh.; Jafar, Eka Sufartianinsih (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. Happiness is a positive emotional state that can be observed and felt, and it varies between individuals. This study aims to determine whether there is a relationship between pet attachment and happiness in early adulthood. The participants in this study consisted of 201 individuals aged 20 to 29 years who owned pets. This research uses a quantitative method and purposive sampling. The instruments used were the Oxford Happiness Questionnaire (23 items; α = 0.872) and the Lexington Attachment to Pets Scale (16 items; α = 0.818). Data were analyzed using Spearman’s rho as a non-parametric correlation test to assess the relationship between pet attachment and happiness. The results showed no significant relationship between pet attachment and happiness in early adulthood (p = 0.350). This finding indicates that attachment to pets does not correlate with happiness. Data were also analyzed using the Mann-Whitney and Kruskal-Wallis tests to assess the significance of pet attachment and happiness between gender and groups of different durations of pet keeping. Additionally, the study found differences in happiness and pet attachment based on gender and duration of pet(s) keeping. The study also found that the duration of ownership contributes to happiness. This study indicates that pet ownership does not necessarily contribute to owners’ happiness, suggesting the need to consider other factors.Keywords: Early adulthood, happiness, pet attachment